(untitled) (Global Journal of Human-Social Science, 2018)
In their pioneering paper titled Introducing Human Rights and Literary Forms or The Vehicles and Vocabularies of Human Rights Sophia A McClennen and Joseph R Slaughter assert perhaps human rights offered a relatively safe framework for humanities scholars to analyze abuses of power and to consider the grievances of the despised and dispossessed McClennen Slaughter 2009 p 5 In my present explication I shall make a humble attempt to use the safe framework of human rights in order to uphold how Indian Dalit literature offers a window to look at the abuses of power by the upper caste Hindus I shall also try to uphold how Indian Dalit literature in general inscribes the life of the Dalits as the despised and dispossessed in the face of caste-ridden Indian society In other words I shall concentrate to theorize upon the general tendency of Indian Dalit literature through the lens of Human rights Indeed in authentically representing the Indian Dalits as the despised and dispossessed Indian Dalit literature is telling the truth to power and at the same time so doing the Indian Dalit writers are not only building a wall of resistance to the conventional codes of living and writing which upper caste Hindus and canonized writers respectively imposed on the Dalits in Indian society but demanding to have those Six Fundamental Human Rights which the honorable Constitution of India preaches to be realized by every human being in India as well